Attitudes of Roma adults towards the care of their elderly relatives - Godó, Irén; Tóth, Dalma (Magyar Gerontológia, 2021)
Caring for the elderly is a challenge for any society even if it is a family or institution related issue (Bánlaki 2006). Numerous researches on the care of the elderly have been published, which help to make the care of the elderly as effective as possible (Djellal, Gallouj 2006). Within the framework of our research, we undertook to examine the attitudes (Arlotti, Aguilar-Hendrickson 2017) and experiences of the Roma towards elderly care.Our aim was to explore the opinions of adult Roma people on the topic, as well as to identify possible cultural peculiarities in this issue (Hajime et al 2006; Da Roit 2010; Kehusmaa et al. 2013; Szabóné 2018).Method:We have selected Roma adult people living in Budapest as our target group, most of them perform manual labour, who in the near future are likely to face the issue of caring for their elderly relatives or are already facing it in the capital. We have chosen this target group because there is a wide range of social services in the capital, and this gives us an insight into the confidence or lack of confidence in the social care system. The situation of the Roma elderly in the Hungarian social context is discussed with a nuanced approach based on Roma studies. The opinions and thoughts of 20 Roma adults are highlighted in our presentation, with whom we interviewed. We compiled a semi-structured set of questions for the target group. We tried to capture the attitude of the Roma towards elderly care along different dimensions (Allport, Lindzey 1960; Örkény, Vári 2009): individual responsibility (Nárai 2019) patterns of the family (Bánlaky 2001), financial and other resources (Bourdieu 1999) - assistance, trust in the social care system, readiness for elderly care (Heimlich 2008). Our research was carried out in November 2021 in compliance with the measures associated witht he COVID-19 situation. The interviews took 40-75 minutes long on average per person.We compare international trends within formation on elderly care in Hungary and data on the health status of elderly Roma in Hungary (Kodner, 2006).Results:The uniqueness of our research lies in the fact that we present the strategies of the Roma related to care in the Hungarian social reality, we identify practical problems and challenges, which can even be a breeding ground for future social policy measures (Schwiter et al. 2015). Poverty among the Roma, as well as discrimination and lower life expectancy compared to non-Roma (KSH, 2015) all contribute to the decision-making of Roma adults regarding the care of their elderly relatives, which is confirmed by the answers found in the interviews and the possibilities and strategies formed by the elderly care system (Kovács 2006). Our results showed that access to various social benefits, such as home help and public health care among others is affected during elderly care, and also has a key role to play, but also information among the Roma. In addition to trust in the social care system, financial means or lack of the influence coping strategies for elderly care. The results obtained can be used even for prevention projects aimed at local health preservation, or for any program aimed at improving the health status of the Roma.ReferencesAllport, G. W., Vernon, P. E., Lindzey, G. A. (1960): A study of values, 3rd ed., Boston, Houghton.Mifflin.Barbara Da Roit (2010): Strategies of Care. Changing Elderly Care in Italy and the Netherlands. Care and WelfareBánlaky Pál (2001): Családszociológia. Wesley János Lelkészképző Főiskola, Budapest.Bánlaky Pál (2006): A család belső működése – A családon belüli kapcsolatok dinamikája. In: Czibere Ibolya (szek.) (2006): Családszociológia szöveggyűjtemény. Debrecen.Bourdieu, Pierre (1999): Gazdasági tőke, kulturális tőke, társadalmi tőke. In: Angelusz Róbert (szerk.): A társadalmi rétegződés komponensei. Budapest, Új Mandátum Könyvkiadó, 156-177.Faridah Djellal, Faïz Gallouj (2006): Innovation in care services for the elderly. The Service Industries Journal. Volume 26, 2006 - Issue 3Hajime Orimo,Hideki Ito,Takao Suzuki,Atsushi Araki,Takayuki Hosoi, Motoji Sawabe (2006): Reviewing the definition of “elderly”. Geriatrics Gerontology, Volume 6, Issue 3 149-158.Helmich K. (2008): A generativitás fogalma és a nemzedékek egymásrahatása. In: Gyáni G., Láng M. (szerk.): Generációk a történelemben. Hajnal István Kör – Társadalomtörténeti Egyesülete és a Nyíregyházi Főiskola Gazdasági Társadalomtudományi Kara, Nyíregyháza (2008) 115-120.Karin Schwiter, Christian Berndt, Jasmine Truong (2015): Neoliberal austerity and the marketisation of elderly care. Social & Cultural Geography Volume 19, 2018 - Issue 3: Placing care in times of austerityKodner, D., and C. Spreeuwenberg. 2002. “Integrated Care: Meaning, Logic, Applications andImplications – A Discussion Paper.” International Journal of Integrated Care Vol. 2 (October-December).Kovács Éva (2006): Mari ésaz ő „cigánysága” – avagy a narratíva helye és ereje az etnicitás kutatásában. Tabula, 2006 9 (I):41-52.KSH Statisztikai Tükör (2015). A hazai nemzetiségek demográgiai jellemzői. https://www.ksh.hu/docs/hun/xftp/stattukor/nemzetiseg_demografia.pdf (Utolsó letöltés ideje: 2021. 11. 03.)Marco Arlotti, Manuel Aguilar-Hendrickson (2017): The vicious layering of multilevel governance in Southern Europe: The case of elderly care in Italy and Spain. Social Policy Administration, Volume52, Issue3, May 2018, 646-661.Margaret McAdam (2008): Frameworks of Integrated Care for the Elderly: A Systematic Review. Ontario Ministry of Health and Long-Term Care.Nárai Márta (2019): A lokális társadalmi szerepvállalás, felelősségvállalás szereplői – egyesületek, alapítványok a helyi közösségek/helyi társadalom szolgálatában, Ünnepi tanulmánykötet a 70 éves Gáspár Mátyás tiszteletére, Magánkiadás, 151-161.Örkény Antal – Vári István: Szempontok és kérdőjelek a magyarországi roma kisebbség tanulmányozásához. Fundamentum, 2009. 2. szám, 5-15.Sari Kehusmaa, Ilona Autti-Rämö, Hans Helenius, Pekka Rissanen (2013): Does informal care reduce public care expenditure on elderly care? Estimates based on Finland’s Age Study. BMC Health Services Research 13, 317.Szabóné dr. Kármán Judit (2018): A magyarországi cigány/roma népesség kulturantropológiai és orvosantropológiai megközelítésben. Romológiai füzetek 2. DRHE, Debrecen, 5-76.